Philippines : Report for the June 2005 Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the Post-Program Monitoring highlights economic developments, fiscal policy, and monetary policy. The primary risk to the near-term outlook for the Philippine economy is that the prevailing state of uncertainty proves to be protracted and sidelines economic reforms. Adverse developments in international capital markets are another potential risk. Executive Directors stressed the importance of the authorities pressing ahead with the implementation of their comprehensive reform package in the fiscal, power, and banking sectors, to reduce the vulnerabilities of the Philippine economy.